Transfer pricing and the limits of legal certainty - A comparability analysis of legality, legal certainty, and economic reality in Danish transfer pricing regulation - Poulsen,Dennis Andreas (2026)
This thesis examines the compatibility of the Principle of Economic Reality against the Principle of Legality in Danish law and the Principle Legal Certainty in EU law within the context of Danish transfer pricing regulation. Utilizing the legal dogmatic method, the thesis establishes the principles and the Danish transfer pricing framework. It then employs the Dubai A case as a central case study to analyse the progression from technical pricing adjustments between controlled entities to substantive reclassification as a masked dividend. The analysis undertaken demonstrates that the Danish transfer pricing framework operates within a structurally dual system in which formally rule-based standards are increasingly supplemented, and in practice, displaced by, discretionary substance based assessments. It demonstrates that the current framework shifts the determination of tax liability from ex ante compliance to ex post evaluation, creating a structural mismatch which struggles to maintain balance between the principles. Despite this mismatch, however, the thesis argues that substantive evaluation may be a necessity of transfer pricing due to the nature of transactions between controlled entities and in totality concludes that the principles are compatible only in a limited and conditional sense with proposed safeguards to ensure better balance.
Keywords: Transfer Pricing; Principle of Legality; Principle of Legal Certainty; Principle of Economic Reality; EU-law; International Trade and Tax law; ex post; ex ante; cumulative discretion; reclassification; masked dividend